Desktop Web-Based Masterbook Application Implementation at SDN 7 Gedongtataan - Novenda Febriana, Tuti Puspita Sari (International Journal of Artificial Intelligence and Robotic Technology (IJAIRTec), 2022)
The implementation of the Parent Book Application at SDN 7 Gedongtaaan based on a desktop web is a design that aims to make it easier for SDN 7 Gedongtaaan teachers to input the value of student learning outcomes data, student biodata, school profiles, school file archives so that if the data is needed it will be shared such as learning outcomes to students of SDN 7 Gedongtaaan. Because so far SDN 7 Gedongtaaan does not yet have a Desktop Web-Based Main Book Application and does not yet have the identity that SDN 7 Gedongtaaan has a Main Book Application, with this, a Desktop Web-based Main Book Application was created as the identity of SDN 7 Gedongtaaan where SDN7 Gedongtaaan has a Desktop Web Application. The process of making a Desktop Web-based Main Book Application at SDN 7 Gedongtaaan using DAD (data flow diagrams), DFD (flow diagrams) and Flowchart diagrams, and designed using Visual Studio Code, Java Script Program Language using the Quasar Framework at SDN 7 Gedongtaaan, With It is hoped that the Desktop Web-Based Main Book Application can help SDN 7 Gedongtaaan teachers and can become an identity application for SDN 7 Gedongtaaan.